Responsible Supply Chain Management - Ewa MAZUR-WIERZBICKA (Communications of International Proceedings, 2021)
The aim of this paper is to demonstrate the synergy between the concept of corporate social responsibility and the concept of a supply chain. The article’s design is intended to achieve this objective: it sheds light on the corporate social responsibility (CSR) concept and supply chain problems, it presents the implementation of the CSR concept in a supply chain and it points to tools used to include corporate social responsibility in supply chain management. The article’s objective and a review of literature addressing the problem at issue allow for the following hypotheses to be formulated: 1. A responsible supply chain is no longer only fashion, but it is mainly a must for companies’ survival and development in the long run. 2. Increased importance of corporate social responsibility is reflected in the implementation of the supply chain concept.
Keywords: Corporate Social Responsibility; Supply Chain; Responsible Supply Chain Management